2018
DOI: 10.1101/255935
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visualizing BDNF cell-to-cell transfer reveals astrocytes are the primary recipient of neuronal BDNF

Abstract: Brain-derived neurotrophic factor (BDNF) is essential for neuronal growth, differentiation, and synaptic plasticity. Although the release and effects of BDNF have been well-studied separately, the transfer of BDNF between cells has not been investigated. Using a fourfluorophore imaging approach to identify both the cell of origin and target cells, we quantified transfer of BDNF. Surprisingly, we found that astrocytes are the main recipient of neuronally expressed BDNF. We further found that astrocytes specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 72 publications
(86 reference statements)
1
13
0
Order By: Relevance
“…Interestingly, TBS activity is likely to induce elevated extracellular potassium levels. Consistent with this, BDNF release from astrocytes was also shown to be induced by elevated extracellular potassium concentration (Stahlberg et al 2018;Vignoli and Canossa 2017). However, HFS was ineffective in releasing recycled BDNF from pure astrocytic cultures (Bergami et al 2008).…”
Section: Bdnf Release From Astrocytessupporting
confidence: 55%
See 1 more Smart Citation
“…Interestingly, TBS activity is likely to induce elevated extracellular potassium levels. Consistent with this, BDNF release from astrocytes was also shown to be induced by elevated extracellular potassium concentration (Stahlberg et al 2018;Vignoli and Canossa 2017). However, HFS was ineffective in releasing recycled BDNF from pure astrocytic cultures (Bergami et al 2008).…”
Section: Bdnf Release From Astrocytessupporting
confidence: 55%
“…Whether neuronal and astrocytic recyclings of BDNF coexist or whether they are successive processes need to be clarified. In contrast to the endocytosis of pro-BDNF, another study suggests that solely the mature form of BDNF is endocytosed by astrocytes via truncated TrkB receptors in dissociated cultures (Stahlberg et al 2018). Interestingly, inflammatory stimuli like released interferongamma increased astrocytic expression of truncated TrkB, which was associated with increased BDNF recycling capacity of astrocytes (Rubio 1997).…”
Section: Bdnf Release From Astrocytesmentioning
confidence: 99%
“…Our previous study demonstrated that the activation of mTORC1 induced by Rheb(S16H) transduction of hippocampal neurons causes BDNF production, which protects against thrombin-induced neurotoxicity in the rat hippocampus [16]. Another study showed that astrocytes are the primary recipient cells of neuronal BDNF in the visual system [39]. Astrocytic CNTF mediates neuronal survival, neurogenesis, and neuronal plasticity through CNTFRα binding in the central nervous system [40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to consider that CB1 also acts as a Gq-coupled receptor, althoush this mechanism is mostly found in slial cells [for review see (Oliveira da Cruz et al, 2016)], and these cells uptake rather than release BDNF (for example (Stahlbers, Kuesler & Dean, 2018). Therefore a CB1-mediated release of BDNF upon calcium influx is an unlikely scenario for the activation of TRKB.…”
Section: Discussionmentioning
confidence: 99%